Autologous Human Dendritic Cells from XDR-TB Patients Polarize a Th1 Response Which Is Bactericidal to Mycobacterium tuberculosis - Rolanda Londt; Lynn Semple; Aliasgar Esmail; Anil Pooran; Richard Meldau; Malika Davids; Keertan Dheda; Michele Tomasicchio (Microorganisms)
Extensively drug-resistant tuberculosis (XDR-TB) is a public health concern as drug resistance is outpacing the drug development pipeline. Alternative immunotherapeutic approaches are needed. Peripheral blood mononuclear cells (PBMCs) were isolated from pre-XDR/XDR-TB (n = 25) patients and LTBI (n = 18) participants. Thereafter, monocytic-derived dendritic cells (mo-DCs) were co-cultured with M. tb antigens, with/without a maturation cocktail (interferon-γ, interferon-α, CD40L, IL-1β, and TLR3 and TLR7/8 agonists). Two peptide pools were evaluated: (i) an ECAT peptide pool (ESAT6, CFP10, Ag85B, and TB10.4 peptides) and (ii) a PE/PPE peptide pool. Sonicated lysate of the M. tb HN878 strain served as a control. Mo-DCs were assessed for DC maturation markers, Th1 cytokines, and the ability of the DC-primed PBMCs to restrict the growth of M. tb-infected monocyte-derived macrophages. In pre-XDR/XDR-TB, mo-DCs matured with M. tb antigens (ECAT or PE/PPE peptide pool, or HN878 lysate) + cocktail, compared to mo-DCs matured with M. tb antigens only, showed higher upregulation of co-stimulatory molecules and IL-12p70 (p < 0.001 for both comparisons). The matured mo-DCs had enhanced antigen-specific CD8+ T-cell responses to ESAT-6 (p = 0.05) and Ag85B (p = 0.03). Containment was higher with mo-DCs matured with the PE/PPE peptide pool cocktail versus mo-DCs matured with the PE/PPE peptide pool (p = 0.0002). Mo-DCs matured with the PE/PPE peptide pool + cocktail achieved better containment than the ECAT peptide pool + cocktail [50%, (IQR:39–75) versus 46%, (IQR:15–62); p = 0.02]. In patients with pre-XDR/XDR-TB, an effector response primed by mo-DCs matured with an ECAT or PE/PPE peptide pool + cocktail was capable of restricting the growth of M. tb in vitro.